so we need to plug in y into our equation so our new equation is:
4x - 2(x+1.75) = 4
first lets distribute the 2 by multiplying the values inside the parentheses by 2
4x - 2x + 3.5 = 4
4x - 2x = 2x
so now our equation is 2x + 3.5 = 4
we need to get x by itself on one side of the parentheses so lets move the 3.5 by subtracting by 3.5 on both sides
2x + 3.5 = 2x
4 - 3.5 = .5
new equation: 2x = .5
now to get rid of this 2 (being multiplied by x) we simply have to do the opposite - divide by 2 on each side
2x/2 = x
.5/2 = .25
so our x value is equal to .25!
if you have any questions about how i answered this question please let me know:)